Effect of Leaching with Distilled Water on a CaCoÂ3-Mixed Na-soil - Mondal, R C (Annals of Arid Zone, 2016)
Leaching with distilled water was done for 29 days of a Na-soil in the presence and absence of CaCO3 (Kankar). The presence of the dolomitic CaCO3 in the Na-soil increased several times the rate of leaching. In the absence of CaCO3, very small fraction of the exchangeable Na could be removed through hydrolysis hut in the presence of CaCO3 comparatively large fraction of the exchangeable Na was replaced by Cn nnd Mg releJsed from CaCO3•